Theoretical Study of The Aspiration System of Pollution Removed from Cotton - A.P.Parpiyev; B.N.Kuziyev; H.G’.Turdiniyozova (Zien Journals, 2024)
In the article, we determine the conditions for ensuring the pneumatic transfer of small impurities separated from the section of the sawed drum of the cleaners by moving steadily without stopping in the dirt hopper
Keywords: warp; inclined surface; cotton balls